THE PERFECTION OF CHATGPT IN MAKING FAST-ACCURATE REPORTS OF STUDENTS AT SMK PARUNG - Taswanda Taryo; Ahmad Musyafa; Uliyatunisa (Abdi Jurnal Publikasi, 2025)
ChatGPT is an artificial intelligence (AI) system that can interact with users through a conversational format. Anyone can use ChatGPT to read and understand the contents of files or enter questions into the ChatGPT interface, allowing the AI ​​to analyze and answer questions on various topics. The ChatGPT training program for Parung Vocational High School (SMK) was conducted to improve students' digital literacy and writing skills. Amid rapid technological advances, the integration of artificial intelligence (AI) into the learning process has become an urgent need. Through this activity, participants were introduced to ChatGPT as a digital aid that can be used to compile report outlines, improve spelling and sentence structure, and enrich written/report content quickly, precisely, and accurately. The workshop was designed based on hands-on practice, where students were trained to actively use ChatGPT features in completing their academic assignments and vocational projects. Evaluation of the activity showed that students improved their understanding of how to write reports that were coherent, logical, and adhered to writing standards. Furthermore, students became more confident and confident in expressing their ideas in writing. With this approach, the workshop not only strengthened academic skills but also taught the responsible and beneficial use of AI technology in vocational education.